A Visible Witness : Christology, Liberation, and Participation - Martinez Olivieri, Jules A. (Emerging scholars., 2016)
A Visible Witness presents a fresh, innovative perspective on a vital movement in twentieth-century theology. Protestant theology in Latin America emerged over fifty years ago, side-by-side with the initial development of Roman Catholic liberation theology. Both traditions have common theological interests: the praxical nature of theology, Christology, and soteriology. Protestants also share some of the fundamental intuitions of liberation theology: the centrality of praxis in Christian life and the priority of opting for the suffering masses. Key Protestant theologians like Jose Miguez Bonino, Nancy Bedford, and Guillermo Hansen challenged Protestant theology in Latin America to develop a Trinitarian hermeneutic for Christology in order to see the work of salvation as the work of the triune God, and to relate Christology and pneumatology in ways that fundamentally shape the praxis of the church. This dissertation takes on this challenge and proposes a theodramatic Christology that serves to ground the Christian notion of salvation as historical liberation and the church's participation in the present experience of redemption in the Trinitarian and economic work of Jesus Christ. The ecclesia of believers participates in God's communicative activity via union with Christ--the community of disciples becomes a theater of liberation.